2009
DOI: 10.1182/blood-2008-03-147967
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling mediates G1/S cell-cycle progression in T cells via cyclin D3 and its dependent kinases

Abstract: IntroductionNotch proteins are a family of ligand-activated large (300 kDa) single-pass transmembrane heterodimeric receptors. 1 Notch controls multiple cell fate decisions and differentiation processes during lymphocyte development and function and is required at various stages of T-cell development. 2,3 Deregulated Notch signaling during T-cell development leads to malignant transformation, including the cancer most closely associated with aberrant Notch expression in humans, acute T-cell acute lymphoblastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
145
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(162 citation statements)
references
References 53 publications
12
145
2
2
Order By: Relevance
“…The former included CCND3, which encodes a cyclin necessary for G1/G2 transition (39) via direct binding to the gene promoter, consistent with a previous report in T-ALL (40). Among the latter, BCL2 and MCL1, two antiapoptotic genes with a well-established role in the pathogenesis of CLL, emerged as novel targets of NOTCH1, likely regulated through long-range dynamic interactions (24,(41)(42)(43).…”
Section: Notch1supporting
confidence: 59%
“…The former included CCND3, which encodes a cyclin necessary for G1/G2 transition (39) via direct binding to the gene promoter, consistent with a previous report in T-ALL (40). Among the latter, BCL2 and MCL1, two antiapoptotic genes with a well-established role in the pathogenesis of CLL, emerged as novel targets of NOTCH1, likely regulated through long-range dynamic interactions (24,(41)(42)(43).…”
Section: Notch1supporting
confidence: 59%
“…Isolated examples in the literature reported enhanced RBPJ binding on the promoters of cyclin D3 and Hes1 in mammalian cells following Notch pathway activation (Fryer et al 2004;Joshi et al 2009). In those studies, enriched RBPJ occupancies were shown by semiquantitative PCR analysis on chromatin-immunopurified material.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting reports exist about the role of Notch in CD4 + T-cell expansion. Some studies concluded that Notch stimulates proliferation of CD4 + T cells; others found it to be inhibitory (13)(14)(15)(16)(17). Notch may have distinct roles in CD4 + T cells under different conditions, but some of the reported discrepancies might stem from experimental factors.…”
mentioning
confidence: 96%
“…Notch may have distinct roles in CD4 + T cells under different conditions, but some of the reported discrepancies might stem from experimental factors. For instance, some studies targeted the γ-secretase, which does not selectively affect cleavage of Notch only, but also of other substrates (15)(16)(17)(18). Also, antibody-mediated activation of Notch may not faithfully mimic the function of natural ligands (15).…”
mentioning
confidence: 99%